Implant-supported prosthesis on it sweeps in reconstruction maxillary for fibula graft. - Huamaní Mamani, Jorge Omar (2005)
The development of microvascular technigues enabling the use of free vascularized bone grafts represents an important advance in the treatment of maxillary defects. The advantages of the fibula are that they offer an abundant supply of tubed bicortical bone for reconstruction of segment defects across the midline, it allows the possibility of subsequent insertion of dental implants. The fibula is considered as the best donor site for long-span reconstruction and offers several advantages compared with ilium, scapula, and radius. The ossointegration has revolutionized the dental rehabilitation, in auddition the use of three dimensional computed tomography and biomodels had made the planning and execution of complex craniomaxillofacial cases more precise. Due to tbe high long term succes (rate of prosthetics restorations with implants more than 90%) inmediate or delayed implants. This technic should be considerer in maxillofacial reconstruction, Additional bone grafting procedures, including the vertical distraction of the grafted fibula are used to achieve adequate function and aesthethics results.